The practices of global and traditional management characteristics among senior managers in Malaysian cooperatives - Mhd. Sarif, Suhaimi; Yusof, Ismail (2010)
The practices of global and traditional management characteristics among senior managers in Malaysian cooperatives are important to ensure the survival and performance of Malaysian cooperatives. Senior management plays a very significant role to enhance the profitability of the co-operatives. Unlike traditional companies which are regulated by the Commission of Companies Malaysia, cooperatives are regulated by the Cooperative Commission of Malaysia. Despite operating under different legal framework, cooperative managers are adopting the characteristics of global managerial traits. This paper attempts to investigate the perceptions of cooperatives’ senior management toward managerial roles and global skills, and aggregate the two sets of dimensions into broader categories.